Ecocriticism and Geopoetics: Ecopsychological Landscapes - Đurković, Uroš (Poznańskie Studia Slawistyczne, 2022)
Based on comparative research on ecocriticism and geopoetics ( Kenneth White) as two theoretical discourses concerning the relationship between literature and environment, the aim of this paper is to explore the connection between literary landscapes and their psychological foundation. Ecocriticism, as a dynamic, complex, and sometimes inconsistent system of thinking about nature and literature, can be enriched byWhite’s geopoetics, which has not only a theoretical but also an important practical dimension. A question of landscape in art is viewed, through these theoretical positions, as one of the crucial moments for personal and collective human self-identification in environment.